Socioeconomic and geographical inequalities in health care coverage in Mozambique: a repeated cross-sectional study of the 2015 and 2018 national surveys - Daca, Chanvo S. L.; Sebastian, Miguel San; Arnaldo, Carlos; Schumann, Barbara; Namatovu, Fredinah (BMC public health, 2023)
Background Over the past years, Mozambique has implemented several initiatives to ensure equitable coverage to health care services. While there have been some achievements in health care coverage at the population level, the effects of these initiatives on social inequalities have not been analysed. Objective The present study aimed to assess changes in socioeconomic and geographical inequalities (education, wealth, region, place of residence) in health care coverage between 2015 and 2018 in Mozambique. Methods The study was based on repeated cross-sectional surveys from nationally representative samples: the Survey of Indicators on Immunisation, Malaria and HIV/AIDS in Mozambique (IMASIDA) 2015 and the 2018 Malaria Indicator survey. Data from women of reproductive age (15 to 49 years) were analysed to evaluate health care coverage of three indicators: insecticide-treated net use, fever treatment of children, and use of Fansidar malaria prophylaxis for pregnant women. Absolute risk differences and the slope index of inequality (SII) were calculated for the 2015 survey period and the 2018 survey period, respectively. An interaction term between the socioeconomic and geographical variables and the period was included to assess inequality changes between 2015 and 2018. Results The non-use of insecticide-treated nets dropped, whereas the proportion of women with children who were not treated for fever and the prevalence of women who did not take the full Fansidar dose during pregnancy decreased between 2015 and 2018. Significant reductions in the inequality related to insecticide-treated net use were observed for all socioeconomic variables. Concerning fever treatment, some reductions in socioeconomic inequalities were observed, though not statistically significant. For malaria prophylaxis, the SII was significant for education, wealth, and residence in both periods, but no significant inequality reductions were observed in any of these variables over time. Conclusions We observed significant reductions of socioeconomic inequalities in insecticide-treated net use, but not in fever treatment of children and Fansidar prophylaxis for pregnant women. Decision-makers should target underserved populations, specifically the non-educated, poor, and rural women, to address inequalities in health care coverage.